Primary Carcinoid Tumor of the Ileal Efferent Limb of an Ileovesicostomy: A Case Report - Adamantios M. Mellis; Daniel C. Parker; David D. Buethe; Gennady Slobodov (Case Reports in Urology)
We report on the evaluation and management of a 47-year-old white male found to have primary carcinoid tumor of the ileal segment of his diverting ileovesicostomy thirty-five months after initial creation. Subsequent to presentation with intermittent gross hematuria, CT urogram highlights an 8 mm enhancing lesion near the enterovesical junction of urinary diversion. Office cystoscopy confirms presence of a lesion that was later endoscopically resected and found to be a well-differentiated carcinoid tumor. Evaluation with serum markers, direct visualization utilizing endoscopy, and imaging was without finding of alternate primary or metastatic lesions. The patient ultimately had the proximal ileal portion of his ileovesicostomy excised and the distal portion converted into an ileal conduit. After briefly discussing the carcinoid tumor and the carcinoid syndrome it may cause, we review the literature on the incidence of carcinoid tumors in a population requiring the use of intestine in the urinary tract.